Mediation Model of Factors Affecting Virtual Team Performance in UAE Organisations - Abdulla Al Kaabi, Hamad Mohammed; Sidek, Safiah; Abo Mosali, Najmaddin (International Journal of Sustainable Construction Engineering and Technology, 2022)
With the advanced communication technology and working from home concept, many organisations are relied on virtual teams to accomplish business activities across their remote branches or global affiliations. This paper presented the formulation of Model on factors affecting Virtual Team Performance in UAE organisations. The model consisted of two independent variables namely Communication Competence nad Cultural Intelligence constructs, one dependent variable which is Virtual Global Team Performance construct and two mediating variables which are Collaboration and Knowledge Sharing construct. The model was constructed using the questionnaire data collected from 318 respondents who were employee in UAE organizations. After the model was developed, it was assessed at each of measurement compondents for fitness criteria. Once, all the measurement components had achieved the goodness-of-fit criteria, the measurement components were tied up to form structural model according to the conceptual framework. The structural model was evaluated for its ability to meet the fitness criteria where it found that collarotion, communication competene, cultural intelligence and knowledge sharing have positive significant effect virtual global team performance. Furthermore, the positive significance of the mediating effect of collaboration and knowledge sharing is confirmed. This means that knowledge sharing and collaboration can have a significant impact on the success or failure of virtual team performance.